Establishing a Typology for Dogs in the English-Speaking Caribbean - Fielding, William J. (International Journal of Bahamian Studies, 2009)
There is currently confusion in animal welfare circles in The Bahamas and the Caribbean with regard to terminology in connection with dog populations. Speakers and writers use the same words to describe dogs with different levels of care and training: these two aspects are important when considering a domesticated animal.This leads to confusion when reading papers or comparing results from different countries or even different reports from within the same country. At its worst, incorrect use of words can lead to acts of violence against dogs.This paper puts forward a typology for dogs which is based upon the level of care offered to dogs as well as the interaction of dogs with humans.